Identification of candidate genes regulating seed oil content by QTL mapping and transcriptome sequencing in Brassica napus - Xiao, Zhongchun; Zhang, Chao; Qu, Cunmin; Wei, Lijuan; Zhang, Liyuan; Yang, Bo; Lu, Kun; Li, Jiana (Frontiers in Plant Science, 2022)
Increasing oil production is a major goal in rapeseed (Brassica napus) molecular breeding programs. Identifying seed oil content (SOC)-related candidate genes is an important step towards achieving this goal. We performed quantitative trait locus (QTL) mapping of SOC in B. napus using a high-density SNP genetic map constructed from recombinant inbred lines and the Illumina InfiniumTM 60K SNP array. A total of 26 QTLs were detected in three years on A01, A03, A05, A06, A09, C01, C03 and C05, which accounted for 3.69%~18.47% of the phenotypic variation in SOC. Of these, 13 QTLs are reported here for the first time. 1713 candidate genes in the 26 QTLs confidence interval were obtained. We then identified differentially expressed genes (DEGs) between the high- and low-SOC accessions, to narrow down our focus to 21 candidate genes (Y1-Y21) related to SOC, and we will focus on 11 (Y1-Y11) candidate genes that contribute to the formation of high-SOC. In addition to providing insight into the genetic basis of SOC in B. napus, the loci identified and candidate genes in this study can be used in molecular breeding strategies to increase SOC in this important seed crop.